2018
DOI: 10.1111/ijfs.13858
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced utilisation of nonmarketable fish: physical, nutritional and sensory properties of ‘clean label’ fish burgers

Abstract: Summary Four ‘clean label’ formulations for fish burgers made with mechanically separated fish meat were characterised in sensory, textural and chemical terms. The formulations differed in the ratios of European sea bass to rainbow trout (50:50 and 30:70) and the ratios of fish to potato flakes (dry matter ratio, DMR: 2.5:1 and 1.5:1). The sensory profile was mainly influenced by DMR. Recipes with the higher DMR were positively correlated with sandy, dry and crusty attributes, salty taste and overall flavour. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(45 reference statements)
0
2
0
1
Order By: Relevance
“…Food products with a modified texture of fish meat are minced fish, pates, riets and pastas. It is rational to use high-quality fish that is not standard in terms of size characteristics in the technology for the production of the above-mentioned products [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Food products with a modified texture of fish meat are minced fish, pates, riets and pastas. It is rational to use high-quality fish that is not standard in terms of size characteristics in the technology for the production of the above-mentioned products [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of cooking on salmonid flesh is not clear; some authors reported a decline in hardness [66,67] and others an increase [68,69]. Nevertheless, the reason why consumers perceived differences in textural features in line with the laboratory analysis is not clear and should be investigated [70,71].…”
Section: Fillet Analysismentioning
confidence: 99%
“…Em hambúrgueres de pescado, os estudos analisam a sua aceitação inserido na merenda escolar (DE-ANDRADE et al, 2020); agregam valor à matéria-prima de espécies poucos exploradas, desenvolvem um novo produto de conveniência (CASTRO et al, 2020;PACI et al, 2018;PRESENZA ab et al, 2022;PACHEKREPAPOL et al, 2022;MARQUES et al, 2020), reduz o desperdício (HUSEIN et al, 2018;HUSEIN et al, 2020) e podem avaliar novos compostos bioativos, componentes funcionais ou culturas bioprotetoras (CRISTOFEL et al, 2021;DUMAN, 2022;DELFINO et al, 2021;IACUMIN et al, 2022;DE-AGUIAR et al, 2022).…”
Section: Recursos Pesqueiros E Consumo De Pescadounclassified